Cerebrospinal Fluid (CSF) CD8+ T-Cells That Express Interferon-Gamma Contribute to HIV Associated Neurocognitive Disorders (HAND) - Schrier, Rachel D.; Hong, Suzi; Crescini, Melanie; Ellis, Ronald; Pérez-Santiago, Josué; Spina, Celsa; Letendre, Scott (PloS one, 2015)
HIV associated neurocognitive disorders (HAND) continue to affect cognition and everyday functioning despite anti-retroviral treatment (ART). Previous studies focused on mechanisms related to monocyte/macrophage mediated inflammation. However, in the ART era, there is increasing evidence for the involvement of CD8+ T-cells in CNS pathogenesis. To investigate the relationship between T-cell responses and neurocognitive impairment (NCI), cerebrospinal fluid (CSF) and peripheral blood CD4+ and CD8+ T-cell intracellular cytokine (IFNγ, IL-2, TNFα) and lytic marker (CD107a) expression were assessed in HIV infected subjects who underwent comprehensive neurocognitive (NC) evaluation and either initiated or changed ART. Data were collected from 31 participants at 70 visits. The frequency of cytokine expressing T-cells in CSF was significantly higher than in peripheral blood for CD4+T-cells: TNFα, IL-2, IFNγ and CD8+T-cells: IL-2 and IFNγ. Analysis of T-cell activity and NCI as a function of CSF HIV RNA levels suggested a general association between NCI, high CSF CD8+ (but not CD4+T-cell) cytokine expression and CSF HIV RNA <103 copies/ml (p<0.0001). Specifically, CSF CD8+ T-cell IFNγ expression correlated with severity of NCI (r = 0.57, p = 0.004). Multivariable analyses indicated that CSF CD8+T-cell IFNγ and myeloid activation (CD163) contributed equally and independently to cognitive status and a composite variable produced the strongest correlation with NCI (r = 0.83, p = 0.0001). In contrast, CD8+ cytolytic activity (CD107a expression) was negatively correlated with NCI (p = 0.05) but was dependent on CD4 levels >400/μl and low CSF HIV RNA levels (<103 copies/ml). In our longitudinal analysis of 16 subjects, higher CSF CD8+IFNγ expression at baseline predicted NC decline at follow-up (p = 0.02). Severity of NCI at follow-up correlated with level of residual HIV RNA in CSF. Presence of IFNγ expressing CD8+ T-cells, absence of cytolytic CD8+ T-cells, high myeloid activation, and failure of ART to suppress HIV replication in CSF contribute to increased risk of HAND.